Does app-based unguided self-management improve mental health literacy, patient empowerment and access to care for people with mental health impairments? Study protocol for a randomised controlled trial - Christine Knaevelsrud; André Kerber; Ina Beintner; Sebastian Burchert (BMJ Open)
Introduction Mental disorders pose a huge burden to both individuals and health systems. Symptoms and syndromes often remain undetected and untreated, resulting in comorbidity and chronification. Besides limited resources in healthcare systems, the treatment-gap is—to a large extent—caused by within-person barriers impeding early treatment seeking. These barriers include a lack of trust in professionals, fear of stigmatisation, or the desire to cope with problems without professional help. While unguided self-management interventions are not designed to replace psychotherapy, they may support early symptom assessment and recognition by reducing within-person barriers. Digital self-management solutions may also reduce inequalities in access to care due to external factors such as regional unavailability of services.Methods and analysis Approximately 1100 patients suffering from mild to moderate depressive, anxiety, sleep, eating or somatisation-related mental disorders will be randomised to receive either a low-threshold unguided digital self-management tool in the form of a transdiagnostic mental health app or care as usual. The primary outcomes will be mental health literacy, patient empowerment and access to care while secondary outcomes will be symptom distress and quality of life. Additional moderator and predictor variables are negative life events, personality functioning, client satisfaction, mental healthcare service use and application of self-management strategies. Data will be collected at baseline as well as 8 weeks and 6 months after randomisation. Data will be analysed using multiple imputation and analysis of covariance employing the intention-to-treat principle, while sensitivity analyses will be based on different multiple imputation parameters and a per-protocol analysis.Ethics and dissemination Approval was obtained from the Ethics Committee of the Faculty of Educational Science and Psychology at the Freie Universität Berlin. The results will be submitted to peer-reviewed specialised journals and presented at national and international conferences.Trial registeration The trial has been registered in the DRKS trial register (DRKS00022531);Pre-results.